Apex resection treatment on tooth 21 and 22 with suspected radicular cyst - Cahyani, Febriastuti; Saraswati, Widya; Mulyadi, Reyz Pasenda; Wahab, Sofi Arnesti; Halima, Siti Noorraida; Dzulfikri, Ahzahra Indah; Zubaidah, Nanik; Kunarti, Sri; Soetojo, Adioro (Universitas Airlangga, 2024)
Background: Apex resection is the surgical removal of the apex or root end of a tooth. Endodontic failure is the most usual reason of treatment being performed. Retreatment may be the first option for teeth which have been treated conventionally and exhibit a persistent apical lesion. In particular, failures during conventional therapy could hinder results by leading infections to spread to inaccessible apical regions, necessitating surgery. Purpose: This case report aims to describe the management of radicular cyst on previously treated tooth. Case: A 51-year-old male patient came to Soewandhie General Hospital with a complaint of swelling on his hard palate from one year before. The left maxillary incisor has undergone root canal treatment about 1 year ago, but had not been permanently filled. Case Management: The treatments given were retreatment for 21 and root canal treatment for 22, then followed by cyst enucleation and apex resection on both teeth. Conclusion: Apex resection shows a satisfying result for treating previously treated tooth with persistent apical lesion.